Evaluation of real-time PCR and flow cytometry efficiency in rapid detection of carbapenemase-producing Enterobacteriales - Koçer, İpek; Karsligil, Tekin; Sağlam, Mustafa; Arslanyürekli, Uğur; Deveci, İhsan; Şahin, Emel (The Journal of Infection in Developing Countries, 2023)
Introduction: Infections due to carbapenem-resistant Enterobacteriales, which have increased worldwide in recent years, cause concern. This study aimed to rapidly detect carbapenemase gene region by using flow cytometry in Enterobacteriales isolates and to evaluate its efficiency and susceptibility by comparing it with polymerase chain reaction (PCR). Methodology: In the study, 21 isolates obtained from the blood cultures of patients hospitalized in intensive care units and found to intermediate or resistant to at least one carbapenem in the automated system, and 14 isolates belonging to the carbapenem-susceptible Enterobacteriales family were included. Carbapenemase gene regions were investigated by PCR after their susceptibility was determined by disk diffusion method. Bacterial suspensions were treated with meropenem + specific carbapenemase inhibitors (EDTA or APBA) and Temocillin and stained with thiazole orange (TO) and propidium iodide (PI) to show dead/live cell differentiation. Dead/live cell percentages were calculated after reading on the flow cytometer device. Results: In the ROC analysis of the flow cytometry method, the cut-off value, specificity, and susceptibility of PI staining rates for meropenem were found as 14.37%, 100%, and 65%, respectively. It was found that the flow cytometry method was well-compatible with PCR in the detection of the carbapenemase gene region. Conclusions: Flow cytometry will continue to be a promising method for the detection of antimicrobial susceptibility and resistance due to its rapid analysis of many cells and its high compatibility with PCR results.